Artificial Flavin Systems for Chemoselective and Stereoselective Oxidations (Eur. J. Org. Chem. 5/2015). Issue 5 (February 2015) - Cibulka, Radek
Abstract : The cover picture shows 5‐alkylflavin hydroperoxide, which is the active species in oxygenations catalysed by flavinium salts. Binding to the flavin moiety significantly enhances the reactivity of oxygen and hydrogen peroxide allowing various types of oxygenations to proceed under mild conditions with high chemoselectivity. Examples include sulfoxidations, N‐oxidations, Baeyer–Villiger and Dakin oxidations, oxidations of aldehydes to carboxylic acids, or the insertion of oxygen into the rhenium–methyl bond. Artificial flavin‐based catalytic systems have been inspired by flavin‐dependent monooxygenases, which utilize hydroperoxide formed from a flavin cofactor as shown in the mirror. Details are presented in the Microreview by R. Cibulka on915 ff .